2014
DOI: 10.1155/2014/354279
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Roles of the Carotid Body Inflammation in Sleep Apnea

Abstract: Breathing difficulties in sleep are a hallmark of sleep-disordered breathing commonly observed in patients with sleep disorders. The pathophysiology of sleep apnea is in part due to an augmented activity of the carotid body chemoreflex. Arterial chemoreceptors in the carotid body are sensitive to inflammatory cytokines and immunogenic molecules in the circulation, because cytokine receptors are expressed in the carotid body in experimental animals and human. Intriguingly, proinflammatory cytokines are also loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…63 In addition to that, increased leukocytes, adhesion molecules and RAAS mediators have been described within the carotid body, reinforcing this link. 64 Intermittent hypoxia increases the chemoreflex as well, augmenting the production of the aforementioned inflammatory cytokines, promoting ROS production, inducing nicotinamide adenine dinucleotide phosphate (NADPH)-mediated NFkB activation and lowering ROS scavengers such as superoxide dismutase (SOD). 63,65 In addition to that, intermittent hypoxia also augments the expression of AT4 receptors, angiotensinogen and angiotensin-converting enzyme within the carotid body, promoting RAAS and chemoreflex activation.…”
Section: Heart Failure With Reduced Versus Preserved Ejection Fractiomentioning
confidence: 99%
See 1 more Smart Citation
“…63 In addition to that, increased leukocytes, adhesion molecules and RAAS mediators have been described within the carotid body, reinforcing this link. 64 Intermittent hypoxia increases the chemoreflex as well, augmenting the production of the aforementioned inflammatory cytokines, promoting ROS production, inducing nicotinamide adenine dinucleotide phosphate (NADPH)-mediated NFkB activation and lowering ROS scavengers such as superoxide dismutase (SOD). 63,65 In addition to that, intermittent hypoxia also augments the expression of AT4 receptors, angiotensinogen and angiotensin-converting enzyme within the carotid body, promoting RAAS and chemoreflex activation.…”
Section: Heart Failure With Reduced Versus Preserved Ejection Fractiomentioning
confidence: 99%
“…63,65 In addition to that, intermittent hypoxia also augments the expression of AT4 receptors, angiotensinogen and angiotensin-converting enzyme within the carotid body, promoting RAAS and chemoreflex activation. 64 Increased chemoreflex response is then able to sustain the inflammatory process promoting phasic hypoxia and SNS overactivation in a vicious circle. The aforementioned mechanisms have been extensively studied for the carotid body and mainly in OSAs, whereas little is known about the role of oxidative stress and inflammation in central apnoea and their effect on central chemoreceptors.…”
Section: Heart Failure With Reduced Versus Preserved Ejection Fractiomentioning
confidence: 99%
“…Regarding the role of the chemoreceptors in the inflammatory response, several studies have shown that glomus cells from the carotid body have receptors for pro-inflammatory cytokines (TNF, IL-6, and IL-1), expressing TLR-4, responsible for LPS recognition ( 45 51 ). Moreover, the administration of LPS increased the expression of TNF and TNF receptor in the carotid body, increasing the immune response ( 46 , 47 ). Thus, the findings of the current study, as well as those from the literature ( 47 ) suggest an immunosensory function of the carotid body as a peripheral sensor for the presence of immunogenic agents from the blood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to androgen excess, oxidative stress and low progesterone might play a role in the observed relationship between PCOS and OSA ( 25 ). Oxidative stress can contribute to the pathogenesis of OSA by causing dysfunction in the carotid body chemoreceptors resulting in ventilatory instability ( 28 ). Progesterone is a respiratory stimulant and can result in lowering upper respiratory resistance ( 29 ).…”
Section: Discussionmentioning
confidence: 99%